Rebound bilirubin levels in infants receiving phototherapy - Taşkin, Erdal; Kiliç, Mehmet; Aygün, A. Denizmen (My University, 2003)
A retrospective medical record review was completed for 854 consecutive newborns receiving phototherapy for hyperbilirubinemia to determine whether a rebound increase in total serum bilirubin (TSB) level occurs after termination of phototherapy. Rebound measurements were included if a bilirubin level was obtained 24 hours after discontinuing phottherapy. The difference between mean TSB levels at discontinuation of phototherapy and at rebound was calculated by Student's test. TSB levels at rebound were significantly lower than at discontinuation of phototherapy for infants weighing >2500 g. There were no statistically significant differences among infants in the smaller weight categories, regardless of Coombs' test results. Infants completing phototherapy for hyperbilirubinemia who are otherwise healthy do not require follow-up solely to identify a rebound bilirubin level.
Yenido?an sariliklarinda fototerapi sonrasi "rebound" hiperbilirübinemi
Keywords: Newborn; Phototherapy; Rebound bilirubin